Examining the ‘hawk-dove effects’ in portfolio assessment using the multi-facet Rasch model - Cobbinah, Andrews; Adu-Mensah, Jephtar (Institute of Advanced Engineering and Science, 2025)
Concerns among students have increased due to the use of test scores in decision-making, leading them to question whether their results accurately reflect their abilities, especially when they perceive subjectivity in rater scoring. This study explores the effects of rater bias on portfolio assessment scores among student teachers in the colleges of education in Ghana. A sample of 207 student portfolios, scored by tutors, was analyzed using a three-facet design model and the FACET software. The findings revealed that tutors exhibited varying rating behaviors, including severity, leniency, and halo effects. These differing rating patterns were found to impact the students’ portfolio scores, suggesting that the subjectivity of raters plays a crucial role in the assessment process.